2017
DOI: 10.1590/1678-992x-2015-0408
|View full text |Cite
|
Sign up to set email alerts
|

Least limiting water range for oil palm production in Amazon region, Brazil

Abstract: In areas cultivated with oil palm, typically mechanized field operations using heavy vehicles may negatively affect soil physical properties and productivity. The aim of this study was to evaluate soil physical quality in an area cultivated with oil palm by monitoring the temporal variation of the soil water content and relating it to the critical limits of the least limiting water range. Soil bulk density (Bd), soil penetration resistance (SR), least limiting water range (LLWR), and water stress days (WSD) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
2
0
3
Order By: Relevance
“…Location 2 had a higher FFB yield mean value compared with the mean FFB yield at location 1. This result is similar to the FFB yield levels reported in OPPs of the Para state and the Amazon region of Brazil [52,53]. The above-mentioned variations in the FFB yield of OPPs is primarily attributed to differences in soil types and soil nutrient status as influenced by nutrient management practices [35,54,55].…”
Section: Ffb Yieldsupporting
confidence: 84%
“…Location 2 had a higher FFB yield mean value compared with the mean FFB yield at location 1. This result is similar to the FFB yield levels reported in OPPs of the Para state and the Amazon region of Brazil [52,53]. The above-mentioned variations in the FFB yield of OPPs is primarily attributed to differences in soil types and soil nutrient status as influenced by nutrient management practices [35,54,55].…”
Section: Ffb Yieldsupporting
confidence: 84%
“…Esta evidência de compactação do solo demonstra a necessidade de que cuidados devem ser tomados para não haver uma maior degradação da qualidade física desse solo, sobretudo na área onde ocorre o tráfego de maquinários. De fato, Sato et al (2017) identificou, na zona de tráfego de área cultivada com palma e óleo, uma degradação da qualidade física do solo, avaliada pelo intervalo hídrico ótimo. Uma redução significativa na biomassa da planta, devido à compactação do solo, foi relatada por Zuraidah et al (2017) em área de cultivo de palma de óleo na Malásia.…”
Section: Resultsunclassified
“…Embora a palma de óleo seja cultivada em diferentes tipos de solos, variações nas propriedades físicas e químicas podem causar diferenças significativas na produção (Woittiez et al, 2017). Avaliando a qualidade física do solo na mesma área estudada, Sato et al (2017) destacou que o estresse hídrico nas profundidades de 20 a 60 cm forneceu evidências de que a variação temporal do conteúdo de água influencia na produtividade da palma de óleo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The LLWR has been used for identifying the limiting factors for plant growth under different tillage systems (Betz, Allmaras, Copeland, & Randall, 1998;Kahlon & Chawla, 2017;Tormena, da Silva, & Libardi, 1999) and soil management and land use (Calonego & Rosolem, 2011;Fidalski, Tormena, & Silva, 2010;Gonçalves et al, 2014;Reichert, da Silva, & Reinert, 2004), including forest soils (Sato, Lima, Ferreira, Rodrigues, & Silva, 2017;Zou, Sands, Buchan, & Hudson, 2000). The estimated da Silva et al (1994) LLWR values for topsoil conditions have been found to be related to crop yield (Beutler et al, 2008;Beutler, Centurion, & Silva, 2005;Lapen, Topp, Gregorich, & Curnoe, 2004).…”
Section: Introductionmentioning
confidence: 99%